Cover Image. Issue 4 (25th March 2018) - Pan, J.; Tong, S.; Tang, J.
Abstract : The cover image, by Jiaqian Pan et al., is based on the Original Article LncRNA expression profiles in HBV‐transformed human hepatocellular carcinoma cells treated with a novel inhibitor of human La protein, DOI:10.1111/jvh.12821 .